Perkembangan Kognitif Masa Anak Anak Awal - Tarigan, Sofie Ahmira Rehgita Br; Syahwitri, Febri Adhari; Salsabila, Fara Naia; Putri, Dhea Aulia (ANWARUL, 2023)
Body size and shape (physical development) are influenced by genetic and environmental factors. Important physical development occurs throughout childhood, namely in the areas of the brain and sympathetic nervous system. However, the personality traits of children, both in terms of their personality and way of thinking, have a significant influence on their development and growth. The authors therefore cover cognitive development in children. Using a quantitative approach, we can conclude that many different things can affect a child's cognitive development; However, in this case, a teacher needs to have a plan to deal with every factor that might have an impact on the cognitive growth of his students. Therefore, the process of cognitive development in children includes progressive learning processes such as attention, memory, and reasoning. The development of these skills is very important so that children can process information, learn to evaluate it, analyze it, remember it, compare it and understand the relationship between cause and effect. That's why kids can improve their learning and thinking skills with some targeted drills and exercises.